2006
DOI: 10.1002/adfm.200600070
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and Electroluminescence from Tris(8- hydroxyquinoline)aluminum Nanowires Prepared by Adsorbent-Assisted Physical Vapor Deposition

Abstract: Single‐crystalline nanowires are successfully prepared from a small organic functional molecule, tris(8‐hydroxyquinoline)aluminum (Alq3), by an adsorbent‐assisted physical‐vapor‐deposition method. The introduction of adsorbents can decrease the sublimation temperature of Alq3, and slow the weight‐loss process markedly, which is proven to be indispensable in improving the uniformity of the as‐prepared Alq3 nanowires. Measurements of the optical properties reveal that the absorption spectra of the Alq3 nanowires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 57 publications
0
103
0
2
Order By: Relevance
“…The preparation and characterization of Alq 3 have been widely studied [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Because of the bidentate ligand, Alq 3 complexes form two isomers, as shown in Figure 1: meridional and facial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation and characterization of Alq 3 have been widely studied [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Because of the bidentate ligand, Alq 3 complexes form two isomers, as shown in Figure 1: meridional and facial.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Alq 3 crystals with a wide range of morphologies have been prepared, including nanoparticles produced by vapor condensation [14], nanowires produced using either a single-step heat treatment [15] or an adsorbentassisted physical vapor deposition (PVD) process [16], pine needle-like crystals produced by PVD [3], and nanorods produced by solution synthesis with a surfactant [17]. All of these Alq 3 crystals demonstrate interesting morphologydependent properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of single-crystalline 1D organic nanostructures were prepared with this method. [157][158][159][160] Figures 7A and B show typical SEM and TEM images of tris(8-hydroxyquinoline)aluminum (Alq 3 ) nanowires. The SAED pattern shown in Figure 7C reveals that the Alq 3 nanowires are single-crystalline structures with preferential growth along the [101] direction, which is also testified by the XRD patterns.…”
Section: Vapor Depositionmentioning
confidence: 99%
“…It was mentioned in Section 2 that Yao's group has developed an adsorbent-assisted PVD strategy for the general construction of crystalline 1D organic nanostructures. [157][158][159][160] It was revealed that the crystallinity of the nanomaterials resulted in some novel luminescent behaviors. In this section, we introduce the fluorescence narrowing and multicolor emission from crystalline nanowires and nanoribbon arrays, respectively, based on a single chemical composition prepared by this method.…”
Section: Unique Luminescence From Crystalline 1d Organic Nanomaterialsmentioning
confidence: 99%